2020
DOI: 10.1002/2211-5463.13010
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the extracellular recombinant Lucky9 xylanase from Bacillus subtilis enhances activity at high temperature and pH

Abstract: In the paper industry, chlorine is often to use to treat the pulp for bleaching. After pulping, a large amount of xylan is present in the fiber. Xylanase can be used to degrade xylan in an eco-friendly process called biobleaching, which can help minimize the usage of chlorine in the delignification process. However, a bottleneck in the adoption of biobleaching is the cost of xylanase and the requirement that xylanase be active and stable at extreme conditions. Here, we investigated whether using sodium alginat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…3 it was observed that, there was much difference in optimum pH of free lipase and immobilized lipase. The optimum pH of free lipase found to be at pH 5 and for immobilized lipase at pH8, these findings revealed that at alkaline pH values, the immobilized lipase exhibited better activity than the free lipase, suggesting that the immobilization enhanced the tolerance of the lipase to alkaline conditions similarly reported by Ding et al, 2020.…”
Section: Effect Of Temperature and Ph On Activity Of Free And Immobilized Lipasesupporting
confidence: 55%
See 1 more Smart Citation
“…3 it was observed that, there was much difference in optimum pH of free lipase and immobilized lipase. The optimum pH of free lipase found to be at pH 5 and for immobilized lipase at pH8, these findings revealed that at alkaline pH values, the immobilized lipase exhibited better activity than the free lipase, suggesting that the immobilization enhanced the tolerance of the lipase to alkaline conditions similarly reported by Ding et al, 2020.…”
Section: Effect Of Temperature and Ph On Activity Of Free And Immobilized Lipasesupporting
confidence: 55%
“…Different organic (e.g. polymers) or inorganic support materials are used for entrapment among that sodium alginate is most widely used polymer due to its low cost, easy to use, mild gelling properties, biocompatibility, thermostability, effective particle size, availability and non toxicity (Ding et al,2020). Hence lipase entrapment in calcium alginate beads has shown to be relatively safe and straightforward techniques so in this study lipase was immobilized using calcium alginate beads (Zusfahair et al, 2020).…”
Section: Issn: 2319-7706 Volume 10 Number 04 (2021)mentioning
confidence: 99%
“…Solid-state fermentation with Enterococcus faecalis was able to reduce pH, destroy plant cell walls, and increase the content of soluble dietary fiber [ 27 ]. Bacillus subtilis were capable of secreting xylanase and β -mannanase, decomposing plant hemicellulose, and reducing the content of non-starch polysaccharides (NSP) and anti-nutritional factors in grain feeds [ 28 , 29 ]. Candida utilis could decompose lignin and cellulose into monosaccharides and ferment them under aerobic conditions as well.…”
Section: Discussionmentioning
confidence: 99%